English teachers curriculum and the competence required by MINED to develop Plan 2021 nationwide - Rodríguez Zelaya, Beatriz Anabell; Galicia Alonso, Luis Alberto; Monterrosa Orellana, Marta Iliana (2024)
In 2004, a new president was elected and during his political campaign, a lot of promises were made. However, the ones that call the attention are those related to education, specially the English area. One of the compromises the president made had to do with Education in a long term. A plan was proposed and was called PLAN 2021. This plan has been implemented by the Ministry of Education in order to improve students' English communicative skills. Therefore, there are some questions that come to our minds as the following: are teachers well prepared to face the new challenges of PLAN 2021? What other things are needed to make this plan successful? Are changes in the curriculum of the major Profesorado en Inglés Para Tercer Ciclo de Educación Básica y Educación Media needed? What is the teacher's profile? What is the teachers' competence required? Due to Plan 2021, the Ministry of Education has been implementing evaluations to measure the proficiency of English teachers and teachers whose specialty is not English but teach “English”. The expectations of the PLAN 2021 are high. Teachers must be able to fulfill the requirements needed to achieve the goals. However, some teachers have gotten a poor level of English, according to data presented by the surveys of the Ministry of Education in "La Prensa Gráfica" published on March 30th ,2005 pages 4b - 9b. Universities, the Ministry of Education and other entities are making their observations on some aspects that influence in the poor performance of most teachers. Besides that, most experts claim for a revision of the current curriculum of the major Profesorado en Inglés Para Tercer Ciclo de Educación Básica y Educación Media.